2010
DOI: 10.1007/s11090-010-9218-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Blacks Produced by Thermal Plasma: the Influence of the Reactor Geometry on the Product Morphology

Abstract: Carbon black (CB) nanopowders were obtained by plasma decomposition of methane at various flow rates using inductively coupled thermal plasma torch system of 35 kW. Nitrogen was also introduced in some experiments along with the methane. Using a cylindrical shape reactor the obtained powders were composed mainly of spherical particles, non-uniform in terms of particles size with diameters between 30 and 150 nm. The shape and size of this reactor resulted in the presence of recirculation areas enabling the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 13 publications
3
28
0
Order By: Relevance
“…Close examination of TEM images (Fig. 7b,d) show a stacking with the same number of graphene planes (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) as in the case of powders produced without nitrogen addition. It can be concluded that the addition of nitrogen along with methane during the production process does not affect the morphology of the material.…”
Section: Powders Produced Without Nitrogen Additionmentioning
confidence: 77%
See 3 more Smart Citations
“…Close examination of TEM images (Fig. 7b,d) show a stacking with the same number of graphene planes (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) as in the case of powders produced without nitrogen addition. It can be concluded that the addition of nitrogen along with methane during the production process does not affect the morphology of the material.…”
Section: Powders Produced Without Nitrogen Additionmentioning
confidence: 77%
“…1. Such geometry provides a gradual gas expansion from the torch to the reactor minimizing both recirculation areas and sudden quenching of the gas [15,16]. A 4 mm annular gap between the ICP plasma torch body Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of a reaction chamber with a conical top region has been investigated by Pristavita et al [30] and by Colombo et al [13], concluding that a finer control of the flow pattern (loss of nanoparticles to the walls) and nanoparticle properties (size) can be achieved thanks to its shape with respect to the cylindrical case. Furthermore, it was shown that the injection of a shroud gas in synergy with the chamber geometry allows to confine the nucleation region away from the walls and to reduce the nanoparticle deposition on them, resulting in higher process yield [13].…”
Section: Nanoparticle Synthesis With a Conical Chambermentioning
confidence: 99%